Development Of Learning Video To Boost Grade IV Students Citizenship Learning Outcomes - Hikmah, Ulfah Nur; Ahmadi, Farid (Universitas Negeri Semarang, 2019)
This study aims to determine the development, feasibility, and effectiveness of video media globalization of learning material in the subjects of Civics 4thgrade SDN 01 Purwoyoso Semarang. This research is a development (Research and Devlopment). The development model used is the Waterfall model. The population in this study are students of SDN 01 Purwoyoso totaled 27 students. Data collection techniques are test and non test. The development consists of five stages: analysis, design, implementation, testing, and maintenance. Results of the assessment of the material validator figures show the percentage of 82.14% to the category of